2014
DOI: 10.5897/ajest2014.1732
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals in vegetables irrigated with Awash River in selected farms around Adama town, Ethiopia

Abstract: A study was conducted at Melka Hida and Wonji Gefersa farms where Awash River was used for cultivation of vegetable crops to assess heavy metal contamination of vegetables. To what extent these vegetables are contaminated is not known. Three leafy vegetable samples, namely, cabbage (Brassica oleracea Linn.), lettuce (Lactuca sativa) and spinach (Spinacea oleracea) from Melka Hida and Wonji Gefersa farms were examined for heavy metal (Cd, Cr and Pb) contamination using atomic absorption spectroscopy. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…Cabbage: The mean concentration of heavy metals in the studied cultivated cabbage irrigated with tin mining pond water was found to be Pb (0.164±0.03), Cu (0.065±0.01), Cd (0.01±0.00), Zn (0.18 ±0.02), Cr (0.11±0.01), Fe (1.49±0.07), Mn (0.17±0.01) and As (0.03±0.01) mg/Kg. The concentration of metals in cabbage irrigated with tin mining pond water is lower compared to the reported literature of 0.22±0.2 mg/Kg and 6.25±1.2 mg/Kg 1.61±0.2 [56], [58], [59] mg/Kg). Similar studies conducted show order of concentration of the heavy metals in is: Fe > Mn > Pb > Zn > Cr > Cu ˃ As ˃ Cd [29].…”
Section: Heavy Metals Accumulation In Cultivated Vegetablesmentioning
confidence: 56%
“…Cabbage: The mean concentration of heavy metals in the studied cultivated cabbage irrigated with tin mining pond water was found to be Pb (0.164±0.03), Cu (0.065±0.01), Cd (0.01±0.00), Zn (0.18 ±0.02), Cr (0.11±0.01), Fe (1.49±0.07), Mn (0.17±0.01) and As (0.03±0.01) mg/Kg. The concentration of metals in cabbage irrigated with tin mining pond water is lower compared to the reported literature of 0.22±0.2 mg/Kg and 6.25±1.2 mg/Kg 1.61±0.2 [56], [58], [59] mg/Kg). Similar studies conducted show order of concentration of the heavy metals in is: Fe > Mn > Pb > Zn > Cr > Cu ˃ As ˃ Cd [29].…”
Section: Heavy Metals Accumulation In Cultivated Vegetablesmentioning
confidence: 56%
“…Asano et al (2007) reported that a large amount of freshwater is diverted to domestic, commercial and industrial sectors, which generate greater volumes of wastewater. However, there is lack of investment capacity worldwide for construction and operation of adequate treatment facilities which threatens the quality of surface water, soils and groundwater to which wastewater is discharged (Girmaye, 2014).…”
Section: Sources Of Wastewater and Irrigated Vegetable Farmingmentioning
confidence: 99%
“…World Bank (2007)estimated that one-quarter of the households in Addis Ababa lack any form of sanitation facility and reported that as a consequence of this they use open spaces, shrubs and river banks to relieve themselves. Girmaye (2014) stated that, among the major rivers in Ethiopia, Awash river flows from central highlands through Ethiopia's major industrial and agro-industrial belt, taking in a whole burden of all types of raw effluent stands as one of the Ethiopian river streams in urban areas of developed rivers. Most of the existing industries and major towns within the upper watershed have no treatment plants for the discharge of their wastes and are seriously polluting the watercourse.…”
Section: Sources Of Wastewater and Irrigated Vegetable Farmingmentioning
confidence: 99%
See 2 more Smart Citations